An Open-Label Feasibility Trial Examining the Effectiveness of a Cognitive Training Program, Goal Management Training, in Individuals With Posttraumatic Stress Disorder - Jenna E. Boyd; Charlene O’Connor; Alina Protopopescu; Rakesh Jetly; Shawn G. Rhind; Ruth A. Lanius; Margaret C. McKinnon (Chronic Stress, 2019)
Background Posttraumatic stress disorder (PTSD) is associated with dysfunction across multiple cognitive domains including executive functioning, attention, and verbal memory. This dysfunction is associated with negative impacts on functional outcomes (e.g., work or social functioning) and reduced response to psychotherapy for PTSD. Despite this knowledge, little work has investigated the efficacy of cognitive remediation strategies in improving cognition and functional outcomes among individuals with PTSD. Objective The current study investigated the efficacy of an established cognitive remediation program, Goal Management Training (GMT), in improving cognitive functioning in a pilot sample of individuals with PTSD symptoms in an inpatient treatment setting. Method Thirty-four inpatients with PTSD symptoms participated in either GMT in addition to treatment as usual (TAU; consisting of psychiatric management, group and individual psychotherapy) (TAU+GMT; n  = 18) or TAU alone ( n =  16). The TAU+GMT group received neuropsychological assessment at baseline and posttreatment, while both the TAU+GMT and TAU groups received assessment with clinical self-report measures at baseline and posttreatment. Results Paired-sample t-tests revealed significant improvements on measures of executive functioning (e.g., response inhibition, cognitive flexibility), processing speed, sustained attention, and verbal memory in the TAU+GMT group. Mixed-design analyses of variance (ANOVAs) revealed a trend toward an interaction effect indicating potentially greater improvements on a measure of the ability to engage in goal-directed behaviors while highly emotional in the TAU+GMT group as compared to the TAU group. Discussion The results of this small feasibility investigation of GMT in PTSD point toward the potential efficacy of GMT in ameliorating cognitive difficulties in individuals with PTSD.